(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The aim of the present study was to develop orodispersible tablets of Baclofen for improving patient compliance, by overcoming the difficulties in swallowing, with the prime objective of arriving at cost effective product by effervescent method. In the effervescent method, mixture of sodium bicarbonate and tartaric acid (each of 12% w/w concentration) were used along with super disintegrants, i.e., treated agar, sodium starch glycolate (SSG), Cross Carmellose Sodium (CCS) and Microcrystalline Cellulose (MCC). The prepared batches of tablets were evaluated for hardness, friability, drug content uniformity, in vitro dispersion time. The hardness and friability test reports revealed that the tablets had a good mechanical strength and resistance. The formulation containing high concentration of MCC, SSC and CCS and mixture of effervescent emerged as the best formulation based on in vitro drug release characteristics. The results of this work suggest that orodispersible tablets of Baclofen with rapid disintegration time, fast drug release and good hardness can be efficiently and successfully formulated by effervescent method.